ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KEPUTUSAN MAHASISWA DALAM MEMILIH JURUSAN AKUNTANSI SEBAGAI TEMPAT KULIAH DI UNIVERSITAS DI KOTA PEKANBARU - Harahap, Fadli; Satriawan, Raja Adri; Hanif, Rheny Afriana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to analyze of the influence of variable cultural, social, personal, and psychological, to the selection of accounting major.This study uses accidental sampling with 100 samples obtained from the calculation formula slovin. Data collection techniques in this study is in the form of questionnaires, while data analysis technique used is multiple regression analysis were processed with SPSS version 17 for Windows. From the results of the testing that has been done, simultaneous regression test (F test) showed that all independent variables studied have a simultaneous effect on the selection of accounting major. Partial regression test (t test) showed that cultural and social variables no effect of the selection major while personal, psychological influence on the selection of accounting majors. The magnitude of the effect caused by Adjusted R2 by four variables together against the dependent variable 40.4%, while the remaining 59.6% is influenced by other variables not examined in this study.Keywords: Influence of cultural, social, personal, psychological, and accounting department.